PENGALAMAN PASIEN HIPERTENSI SELAMA MENJALANI PENGOBATAN PADA MASYARAKAT DI DESA LAUT DENDANG - Mendrofa, Novipriani; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
Background: Hypertension is a health disorder that causes significant harm to patients. The experience of hypertensive patients reflects their perception while undergoing treatment to manage hypertension. Objective: To explore the experiences of hypertensive patients while undergoing treatment in the community of Laut Dendang Village. Methods: This research used a descriptive qualitative method with a phenomenological approach through in-depth interviews in Laut Dendang Village, Percut Sei Tuan Sub-district, Deli Serdang Regency in April 2024. The participants in this study were 8 (eight) individuals selected using purposive sampling. The interview results were analyzed through data reduction, data display, and conclusion drawing according to Moleong. Results: The study identified five themes related to the experiences of hypertensive patients during treatment in Laut Dendang Village: (1) Low knowledge about hypertension treatment, (2) Complaints of hypertensive patients, (3) Use of herbal plants as one method to manage hypertension, (4) Reasons for choosing treatment methods, and (5) Causes of hypertension recurrence. Conclusion: Hypertensive patients still have limited knowledge regarding the proper and regular application of treatment. They reported various physical symptoms and emotional changes during hypertension, utilized herbal plants from fruits and leaves in addition to medical treatment, perceived treatment effectiveness, trusted the treatment system, feared the side effects of medications, and considered the low cost and proximity to healthcare centers as reasons for choosing treatment. Recurrence of hypertension in patients was caused by dietary factors and psychological aspects. Recommendation: Future researchers are encouraged to conduct both quantitative and qualitative studies to identify the challenges hypertensive patients face in treatment.